Peningkatan Kemampuan Berpikir Kreatif Matematis Siswa melalui Model Pembelajaran Missouri Mathematics Project (MMP) - Novi Marliani (Formatif: Jurnal Ilmiah Pendidikan MIPA, 2015)
This research study in the form of literature and aims to look atcreative thinking skills of students through learning mathematical model of Missouri Mathematics Project(MMP). In studying mathematics, think are of central importance. athrequires that every student has the ability to understand the formula, calculate, analyze, categorize objects, making props, create mathematical models, and others. These activities not only require regular thinking activities (convergent), but it takes the ability to think high (divergent). In fact many schools with the ability to thinkis still fairly low. Creative thinking skills can be defined mathematically as theability to solve mathematical problems with more than ones ettlement and students thinks mooth, supple, elaborating, and have originality in the answer. Creative thinking can be beneficial to train mathematical divergent thinking skills in mathematics. There fore, it is necessary to realize the selection of appropriate learning models and effective. One of mathematical learning model that can be used to train and improve students' ability to think creatively is mathematical learning model Missouri Mathematics Project (MMP). Keywords : mathematical creative thinking ability, learning models missouri mathematics project (MMP).